Chapter Attori e strumenti delle politiche per l'innovazione - Lombardi, Mauro (Studi e saggi, 2021)
After explaining a large set of new concepts and proposing a new theoretical frame, we first depict same stereotypical behavioral and strategic propensities emerging in human systems according an important managerial literature. Then we highlight the systemic models emerging from the strategies implemented by some Italian Regions in managing innovation dynamics. The arrival of the analysis is the identification of more effective tools for founding innovation policies.